2018
DOI: 10.3390/nu10040455
|View full text |Cite
|
Sign up to set email alerts
|

A Low Glycaemic Index Diet in Pregnancy Induces DNA Methylation Variation in Blood of Newborns: Results from the ROLO Randomised Controlled Trial

Abstract: The epigenetic profile of the developing fetus is sensitive to environmental influence. Maternal diet has been shown to influence DNA methylation patterns in offspring, but research in humans is limited. We investigated the impact of a low glycaemic index dietary intervention during pregnancy on offspring DNA methylation patterns using a genome-wide methylation approach. Sixty neonates were selected from the ROLO (Randomised cOntrol trial of LOw glycaemic index diet to prevent macrosomia) study: 30 neonates fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 41 publications
1
58
1
1
Order By: Relevance
“…Maternal diet has been shown to influence DNA methylation patterns in offspring, but research in humans is limited ( 117 ). Recently, findings from the ROLO study (Randomized control trial of Low glycaemic index diet to prevent macrosomia) suggested that low glycemic index dietary intervention during pregnancy was associated with subtle, yet widespread differential DNA methylation at regions across the offspring's genome ( 118 ). These data imply that exposure to a dietary intervention may impact the neonatal epigenome and therefore their risk of obesity and NCDs during fetal development, though larger studies are required to fully explore interventions in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal diet has been shown to influence DNA methylation patterns in offspring, but research in humans is limited ( 117 ). Recently, findings from the ROLO study (Randomized control trial of Low glycaemic index diet to prevent macrosomia) suggested that low glycemic index dietary intervention during pregnancy was associated with subtle, yet widespread differential DNA methylation at regions across the offspring's genome ( 118 ). These data imply that exposure to a dietary intervention may impact the neonatal epigenome and therefore their risk of obesity and NCDs during fetal development, though larger studies are required to fully explore interventions in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…because modulated via epigenetic changes [8, 28]. “Subtle but widespread” changes in the DNA methylation were found in the cord blood of babies from the ROLO study, as reported by Geraghty et al [9]. In other words, the intervention might have not impacted foetal metabolism and early infancy anthropometry, but the in-utero exposure to a low-GI diet might still show its beneficial effects in later stages in life.…”
Section: Discussionmentioning
confidence: 87%
“…In the discovery cohort of 60 mother-child pairs, children born from mothers in the intervention group exhibited high variation in DNA methylation, especially in genes related to cardiac and immune functions. These results, however, were inconsistent with those obtained in the replication cohort, and no associations with maternal body mass index (BMI), infant sex, or birthweight were evident [ 38 ].…”
Section: Dietary Interventions During Pregnancymentioning
confidence: 85%
“…It is worth mentioning that observational research associated LINE-1 methylation with several disease in adulthood, including cancer, neurodegenerative diseases, obesity, and metabolic disorders [ 49 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. In 2018, Geraghty and colleagues evaluated the effect of an intervention based on dietetic consulting and written resources to promote healthy dietary habits in general, and low glycemic index diet in particular [ 38 ]. Specifically, women in the intervention group were recommended to follow an eucaloric diet but replacing high glycemic foods with low glycemic alternatives.…”
Section: Dietary Interventions During Pregnancymentioning
confidence: 99%